MUSTN1 and FABP3 interact to regulate adipogenesis and lipid deposition - Yu Fu; Xin Hao; Jingru Nie; Hongliang Zhang; Peng Shang; Bo Zhang; Hao Zhang (Journal of Lipid Research)
Lipid deposition is related to agricultural animal production and human health, and elucidating its molecular regulatory mechanisms is a topic of interest and a challenge in current scientific research. Musculoskeletal embryonic nuclear protein 1 (MUSTN1) regulates growth and development, including muscle tissue; however, its role in fat deposition remains unknown. Thus, our objective was to determine this role. Our new findings were as follows: MUSTN1 was highly expressed in the fat tissue of pigs with strong adipose deposition capacity; functionally, MUSTN1 promoted the proliferation and adipogenic differentiation of porcine and mouse preadipocytes. MUSTN1 knockout mice were protected against HFD-induced obesity, hepatic steatosis, and insulin resistance; and fatty acid binding protein 3 was identified as an interacting protein of MUSTN1, which facilitated preadipocyte proliferation and differentiation by activating the phosphatidylinositol 3 kinase/AKT signaling pathways. This study reveals a positive regulator for fat development, which suggests a novel approach for studying obesity and animal genetic improvement through the modulation of MUSTN1 expression.